Optimization of Fruiting Body Production of Three Kinds Edible Mushrooms Species by Innovate the Incubation Time and Number of Rips on Baglog - Denny Irawati; Naresvara Nircela P; Febe Margareta RM; J.P. Gentur Sutapa (Jurnal Ilmu Kehutanan)
In Indonesia the demand for edible mushroom, both for medicine and food, continues to increase. Production acceleration is needed to meet the market needs. This study aims to determine the effect of the incubation time and the number of rips on baglog to the productivity of 3 species of edible mushrooms that are widely cultivated in Indonesia. The baglog as sample in this study was obtained from Sedyo Lestari mushroom farmer in Bantul. The baglog was inoculated by 3 kinds of mushroom of Auricularia sp. (ear fungus), Pleurotus sp. (oyster mushroom), and Ganoderma sp. (lingzhi mushroom). After inoculation, the medium was incubated for 30, 40, and 50 days, for subsequent cultivation for 60 days. At the end of the incubation period, the glucosamine content was analysed and the baglog was teared at 1 or 2 ends to trigger the appearance of the fruiting body. During the cultivation period, the fruiting bodies were harvested and the productivity of the fruiting body and the harvesting intensity were measured. The results showed that the incubation time and the amount of rips on the baglog gave a different effect on each mushroom species. The duration of incubation time had no significant effect on fruiting body productivity and biological conversion on oyster and ear mushrooms.However, it had a significant effect on Lingzhi mushroom. The best time of incubation for Lingzhi mushroom was 40 days. The amount of rips on the baglog did not give effect to the productivity of oyster and ear mushrooms, but it affected the productivity of Lingzhi mushroom and the harvesting intensity of ear mushroom.